PENGABDIAN DALAM MENGOPTIMALISASIKAN PENGOLAHAN LIDI KELAPA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA PENAGA - Agusven, Tubel; Basyid, Abdul; Santoso, Nanda Kristia; Fatahuddin, Fatahuddin; Ardian, Rizki; Sulasmi, Anggun Putri; Silalahi, Rusmaida; Yanti, Maisarah Putri; Pratiwi, Indah (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Each village has potential, both physical potential such as climate, soil, water, geographical environment, human resources and others as well as non-physical potential such as community culture. One of the potentials found in Penaga Village, Teluk Bintan District. Bintan Regency is abundant marine products such as fish, shrimp, cuttlefish, bark and others. This can be seen from the majority of the Penaga Village community's livelihood as fishermen and their marine catches are still not optimally utilized. Therefore the community service activities process fish into fish crackers to support the economy of the Penaga Village community as an effort to empower the community towards independence in entrepreneurship and optimizing the utilization of potential. The method used is a qualitative method of conducting interviews with village heads, hamlet heads and surrounding communities. Furthermore, a socialization and training program was carried out where this program was one part of the community service program activities in the form of training on how to process fish crackers by utilizing marine catches to become fish crackers so that they could have higher selling value, licensing and business legality, and marketing through digital marketing . It is hoped that after participating in this training, the community will be motivated to develop the potential that exists in Penaga Village